Budaya Jawa dalam Cerpen Mencicipi Semesta Karya Riska Dyah Oktaviani - Kidungjati, Kedasih; Pranata, Gigih Bayu; Baihaqi, Imam (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
Literature is a form of creative activity in which there are cultural elements. Literature can be divided into written literature or oral literature. Meanwhile, culture is a way of life or living habits that develop in society and are passed down from generation to generation. Culture is formed from complex elements, namely religious systems, politics, customs, practices, language, buildings, clothing and works of art. A short story is a literary work written briefly that tells a conflict or event. This research aims to analyze Javanese culture contained in the short story entitled